2011
DOI: 10.1007/s10354-011-0885-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating retinol-binding protein 4 and metabolic syndrome in the elderly

Abstract: RBP4 plays a role in biological mechanisms that are responsible for insulin resistance and development of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
3
11
0
1
Order By: Relevance
“…Therefore, there is a rather broad definition of normal/ healthy serum RBP4 levels, which range from 10 to 50 g/ml, depending on the methodology used in a specific study. Likewise, the relative increase in the serum RBP4 level associated with various disease states, such as obesity, insulin resistance, cardiovascular disease, and type 2 diabetes, can range from 17 to 150 g/ml (8,9,(11)(12)(13)(14)(15)(16)(17)(64)(65)(66)(67). In one particular study (11), about half of the patient samples in which RBP4 levels were measured had serum RBP4 levels above 100 g/ml, which is similar to the serum RBP4 level in young RBP4-Tg mice (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Therefore, there is a rather broad definition of normal/ healthy serum RBP4 levels, which range from 10 to 50 g/ml, depending on the methodology used in a specific study. Likewise, the relative increase in the serum RBP4 level associated with various disease states, such as obesity, insulin resistance, cardiovascular disease, and type 2 diabetes, can range from 17 to 150 g/ml (8,9,(11)(12)(13)(14)(15)(16)(17)(64)(65)(66)(67). In one particular study (11), about half of the patient samples in which RBP4 levels were measured had serum RBP4 levels above 100 g/ml, which is similar to the serum RBP4 level in young RBP4-Tg mice (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…However, in the past decade numerous clinical studies have linked increased serum levels of RBP4 to disease, including obesity (8,9), insulin resistance (8)(9)(10)(11)(12)(13), type 2 diabetes (9, 13), and cardiovascular disease (hypertension, atherosclerosis, stroke) (14)(15)(16)(17)(18)). This appears to be more than a spurious correlation, since recent studies have demonstrated that RBP4 is an adipokine (adipose-derived cytokine) with retinoid-independent, proinflammatory activity that contributes to the development of insulin resistance (13,(19)(20)(21).…”
Section: S Erum Retinol-binding Protein 4 (Rbp4) Is the Sole Specificmentioning
confidence: 99%
“…levated levels of serum retinol-binding protein 4 (RBP4), the transport protein for vitamin A (retinol) in the blood circulation, correlate with insulin resistance and type 2 diabetes in several clinical studies (1,13,25,32,41,49,52,68). Furthermore, studies in mice have shown that ectopic overexpression of serum RBP4 inhibits insulin signaling in muscle and adipose tissues and causes systemic insulin resistance, whereas Rbp4 Ϫ/Ϫ mice have increased insulin sensitivity (8,68).…”
mentioning
confidence: 99%
“…These actions of RBP‐4 have been proposed to result from IR . RBP‐4 levels have been related with not only IR but also metabolic syndrome, type 2 diabetes mellitus, obesity and dyslipidemia …”
Section: Discussionmentioning
confidence: 99%
“…11,20,21 RBP-4 levels have been related with not only IR but also metabolic syndrome, type 2 diabetes mellitus, obesity and dyslipidemia. 11,12,22 Pregnancy is a diabetogenic condition and RBP-4 values continue to rise during gestations of nondiabetic women, generally returning to normal range after delivery. 8 On the contrary, Inoue et al reported that the RBP-4 values were higher in the first trimester and decrease through the second trimester and plateau thereafter in normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%